Pengaruh Formulasi Pakan Hijauan (Rumput Gajah, Kaliandra dan Gamal) terhadap Pertumbuhan dan Bobot Karkas Domba - Firdus Firdus (Agricultural Faculty, 2010)
The effect of forage formulation (elephant grass, kaliandra, and gamal leaves) on the growth and carcass of sheepABSTRACT. Feed is one of most important factors to increase animal production. Feeding animal with only one kind of grass such as elephant grass on ruminant animals including sheep is not able to increase the productivity of the animals. Kaliandra and gamal leaves contain high level of protein and can be formulated to ruminant nutrition. The purpose of this experiment is to evaluate the effect of forage namely elephant grass (Penisetum sp.), kaliandra (Caliandra calothyrsus), and gamal (Gliricidia sepium) on the growth and carcass of sheep. Forty nine sheep with the starting weight of 15,42 kg (SD 2,68) were used in this experiment and fed fresh elephant grass (RGS), fresh kaliandra (KS), dried kaliandra (KKR) and steamed kaliandra (KKS). Treatment A: 70 % RGS + 30 % KS, B: 70 % RGS + 30 % GS, C: 70 % RGS + 15 % KS + 15 % GS, D: 70 % RGS + 15 % KKR + 15 % GS, E: 70 % RGS + 15 % KKS + 15 % GS. Animals were fed for 70 days and given free access of water (ad libitum). Data collection was the growth of animals (average daily gain) and the weight of carcass. All data was analyzed by ANOVA. The results of the experiment show that forage formulation (fresh elephant grass, fresh, dried and steamed kaliandra and fresh gamal leaves) were not significantly effect on the growth and carcass of sheep.